Characteristics of infective endocarditis in a cancer population. Issue 2 (3rd August 2021) - Grable, Cullen; Yusuf, Syed; Song, Juhee; Viola, George M; Ulhaq, Owais; Banchs, Jose; Jensen, Corey T; Goel, Harsh; Hassan, Saamir
Abstract : Background: Infective endocarditis (IE) is more common in patients with cancer as compared with the general population. Due to an immunocompromised state, the need for invasive procedures, hypercoagulability and the presence of indwelling catheters, patients with cancer are particularly predisposed to the development of IE. Objectives: Limited information exists about IE in patients with cancer. We aimed to evaluate the characteristics of patients with cancer and IE at our tertiary care centre, including a comparison of the microorganisms implicated and their association with mortality. Methods: A retrospective chart review of patients with cancer who had echocardiography for suspicion of endocarditis was conducted. A total of 56 patients with a confirmed diagnosis of cancer and endocarditis, based on the modified Duke criteria, were included in the study. Baseline demographics, risk factors for developing IE, echocardiography findings, microbiology and mortality data were analysed. Results: Following the findings of vegetations by echocardiography, the median survival time was 8.5 months. Staphylococcus aureus was the most common organism identified as causing endocarditis. The mitral and aortic valves were the most commonly involved sites of endocarditis. Patients with S. aureus endocarditis (SAE) had a significantly poorer survival when compared with patients without SAE (p=0.0217) over the 12-month period from diagnosis of endocarditis. Conclusions: Overall survival of patients with cancer and endocarditis is poor, with a worse outcome in patients with SAE.